1975
DOI: 10.1007/bf00999930
|View full text |Cite
|
Sign up to set email alerts
|

Acute blood biochemical alterations in response to marathon running

Abstract: Adrenal-sympathico function, blood carbohydrates and lipids, and water and electrolyte balance were studied in six highly trained male marathon runners prior to and after running a marathon (26.2 miles; 42.2 km) and on control days corresponding to the above times. Fluid intake was not sufficient to maintain body weight, the runners losing approximately 2.8 kg. Estimated plasma volume losses (161 ml, 4.4%) indicated that most of the fluid loss was extravascular. Tre rose an average 2.4 degrees C and a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
0
9

Year Published

1986
1986
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 20 publications
10
27
0
9
Order By: Relevance
“…However, in a study by McCarthy and Dale (1988) it was concluded that less than 10% of the leucocytosis could be attributed to dehydration, on the basis of little or no change in haematocrit levels. This view is confirmed by others (Maron et al, 1975;Haq et al, 1993;Castell and Newsholme, 1998).…”
Section: Dehydration and Circulating Cellssupporting
confidence: 84%
“…However, in a study by McCarthy and Dale (1988) it was concluded that less than 10% of the leucocytosis could be attributed to dehydration, on the basis of little or no change in haematocrit levels. This view is confirmed by others (Maron et al, 1975;Haq et al, 1993;Castell and Newsholme, 1998).…”
Section: Dehydration and Circulating Cellssupporting
confidence: 84%
“…Nevertheless, the cortisol response to exercise is stable and common during and/or after short-term exercises with an intensity above the anaerobic threshold (11,22,58,66,90), and in exercises with a duration ofmore than 2 -3 hours (20,62,80,90).…”
Section: Stability and Variability In Hormonal Responses To Exercisementioning
confidence: 99%
“…We have previously shown that plasma concentrations of choline, a precursor for membrane phosphatidylcholine and for the neurotransmitter acetylcholine, decrease in subjects completing a marathon (Conlay et al, 1986). Other authors have documented changes in amino acid profiles, though with varying paradigms and results (DeCombaz et al, 1979;Felig et al, 1971;Ahlborg et al, 1974;Tysper et al, 1980;Holm et al, 1978;Brodan et al, 1976;Maron et al, 1975). Thus, Felig et al (1971) and Ahlborg et al (1974) noted an increase in the plasma concentrations of the amino acid tyrosine in subjects exercising moderately or intensely on a cycle, while Tysper et al (1980), Brodan et al (1976), and Holm et al (t978) failed to observe this increase.…”
Section: Introductionmentioning
confidence: 96%